The importance of circulating tumor products as „liquid biopsies” in colorectal cancer - Alina Miscoci; Cristian D. Pirvu; Veronica Calborean; Costin T. Streba; Otilia C. Rogoveanu; Vlad Pădureanu; Cristin C. Vere (Journal of Mind and Medical Sciences)
Liquid biopsies represent an array of plasma analysis tests that are studied to evaluate and identify circulating tumor products, especially circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA). Examining such biomarkers in the plasma of colorectal cancer patients has attracted attention due to its clinical significance in the treatment of malignant diseases. Given that tissue samples are sometimes challenging to procure or unsatisfactory for genomic profiling from patients with colorectal cancer, trustworthy biomarkers are mandatory for guiding treatment, monitoring therapeutic response, and detecting recurrence.